PENGABDIAN KEPADA MASYARAKAT: SOSIALISASI KEBERSIHAN LINGKUNGAN DI SD NEGERI PIGAPU, KABUPATEN MIMIKA - Yahya Nusa; Ahmad Tomu; Nandika Yuda Pratama Ohoimas; Arum Santi Presilia Santoso; Winda Astika Ohoirenan; Nursalim (JOURNAL OF COMMUNITY DEDICATION, 2025)
The problem of environmental cleanliness in Pigapu village, especially at Pigapu State Elementary School, is still quite high due to the habit of littering and the limited cleaning facilities. This is evidenced by the accumulation of garbage around the school area. This activity aims to instill awareness in students about the importance of maintaining environmental cleanliness from an early age. The activity is carried out in several stages, namely socialization about the importance of cleanliness, practicing recycling waste, and installing educational posters in the classroom area. The results of the activity show a high enthusiasm from the students and a change in behavior, such as starting to throw trash in its place and participating in keeping the classroom clean. This activity emphasizes the importance of early education on cleanliness by involving students as agents of change in the school and home environment.